Four cycles of paclitaxel and carboplatin as adjuvant treatment in early-stage ovarian cancer: A six-year experience of the Hellenic Cooperative Oncology Group - Bamias, A.; Papadimitriou, C.; Efstathiou, E.; Rodolakis, A.; Vlahos, G.; Voulgaris, Z.; Bozas, G.; Fountzilas, G.; Aravantinos, G.; Razis, E.; Gika, D.; Dimopoulos, M.A. (BMC Cancer, 2006)
Background: Surgery can cure a significant percentage of ovarian carcinoma confined to the pelvis. Nevertheless, there is still a 10-50% recurrence rate. We administered paclitaxel/carboplatin as adjuvant treatment in early-stage ovarian carcinoma. Methods: Patients with stages Ia or Ib, Grade 2 or 3 and Ic to IIb (any grade) were included. Patients were treated with 4 cycles of Paclitaxel 175 mg/m2 and Carboplatin [area under the curve (AUC) 6 (Calvert Formula)] every 3 weeks. Results: Sixty-nine patients with no residual disease following cytoreductive surgery and minimal or modified surgical staging were included in this analysis. Grade 3 or 4 neutropenia occured in 29.9% of patients, while neutropenic fever was reported in 4.5%. Neurotoxicity (all Grade 1 or 2) was reported in 50% of cases. Median follow-up was 62 months. 5-year overall survival (OS) and relapse-free survival (RFS) were: 87% (95% confidence intervals [CI]: 78-96) and 79% (95% CI: 69-89), respectively. Significantly fewer patients with stages Ic-IIb and tumor grade 2 or 3 achieved a 5-year RFS than patients with only one of these two factors (73% vs 92%, p = 0.03). Conclusion: Paclitaxel/Carboplatin chemotherapy is a safe and effective adjuvant treatment in early-stage ovarian carcinoma Patients with stages Ic-IIb and tumor grade 2 or 3 may benefit from more extensive treatment. © 2006 Bamias et al; licensee BioMed Central Ltd.